The immigration policy of the European Union: Challenges and prospects ; conclusions for Poland - Janina Witkowska (Comparative Economic Research. Central and Eastern Europe, 2022)
The paper aims to characterize and evaluate the immigration policy of the European Union in the context of the challenges posed by regular and irregular migration processes on a global and regional scale. The EU policy is in line with the United Nations (UN) initiatives aimed at international cooperation in solving migration problems. The provisions of the treaties share powers in EU immigration policy between its institutions and member states. The harmonization of activities in this area is carried out through the implementation of directives adopted at various times and related to limited areas of immigration policy, hence its fragmented nature. The 2015 migration crisis posed new challenges to the EU's immigration policy and revealed conflicts of interest between individual member states. Nevertheless, the EU is taking steps to build a comprehensive approach to migration, asylum, integration, and border management (The New Pact on Migration and Asylum). The diverse position in terms of the balance of migration flows of the EU as a whole (a net importer of labor) and individual member states (e.g., Poland - a net exporter of labor and recipient of circular migration) affects the approach to migration issues and the acceptance of the proposed solutions in the area of migration policy.
Keywords: F02; F15; F22; 330; migration; European Union; the EU immigration policy; Poland; circular migration